P232 The early detection of chronic obstructive pulmonary disease. (16th November 2010) - Gupta, A; Church, S; Lacey, S
Abstract : Introduction: Approximately 835 000 people in England have been diagnosed with COPD however it is estimated that over 3 million have the disease1 and those cases that are diagnosed are mainly moderate or severe in nature.2 The direct cost of COPD to the UK healthcare system is estimated to be between £810m and £930 m per annum 3 and without change is set to grow Methodology: It is essential that we offer good quality early diagnosis but the numbers involved are huge so a screening programme and pathway were developed. Patients at risk of COPD were initially defined as being aged over 40 with a smoking history. Vitalograph COPD6 devices, which measure FEV1 were used across 22 practices to screen the target population at an average test time of 5 min compared to full spirometry of 20 min. All abnormal results were followed up with full spirometry, performed by an accredited health care provider. Results: To date 2055 patients have been screened. 841 (41%) demonstrated an abnormal result on COPD6 screening. Of these so far 376 have had COPD confirmed by spirometry. That is 18.3% of the target population and 45% of the group who had abnormal COPD6 results. It is estimated that, nationally over 2 million people have undiagnosed COPD and of those over 50% are diagnosed with moderate to severe disease2 however the results available to date suggest that early detection leads to the majority of patients being identified while their condition is still mild. Results to date demonstrate that 75% of diagnoses were mild, 18% moderate and 3.2% severe. We are still awaiting confirmation of the remaining 3.8%. The project is ongoing. Outcomes: Mild COPD costs approximately 50% less to treat than moderate COPD and 90% less than severe COPD. 4 Therefore in addition to improving outcomes for patients, early detection will also reduce the burden of care to the NHS and socioeconomic costs.